Diagnostic and treatment dilemma of gingival enlargement: a report of 3 cases (Nigerian Dental Journal, 2012)
Gingival enlargement is a common feature of periodontal disease which is occasionally associated with medication use for systemic conditions such as hypertension and epilepsy. However, other local and systemic factors have been implicated in the aetiopathogenesis of this condition which could pose diagnostic and therapeutic challenge for clinicians. This paper presents the management of three cases of gingival enlargement recently seen at the Dental Centre of the Lagos University Teaching Hospital, Lagos. The association of unusual secondary aetiological factors is emphasized.
Keywords: Gingival Enlargement; Diagnosis; Treatment